ALKALOIDS FROM ARISTOLOCHIA-ARCUATA - Watanabe, L. Y.; Lopes, LMX (Elsevier B.V., 1995)
Phytochemical studies with Aristolochia arcuata led to the isolation of KNO3, fructose, sucrose, sitosterol, calarene, its 2-oxo derivative, and three neolignans. Besides which, two new 13-oxidodibenzo[a, g]-quinolizinium alkaloids were isolated. They present only one oxygenated substituent at rings A and D.
Keywords: ARISTOLOCHIA ARCUATA; ARISTOLOCHIACEAE; POTASSIUM NITRATE; CARBOHYDRATES, ARISTOLANE SESQUITERPENES; SITOSTEROL; TERAHYDROFURAN NEOLIGNANS; 13-OXIDODIBENZO[A,G]-QUINOLIZINIUM ALKALOIDS